Avaliação da mielinização do sistema auditivo de recém-nascidos e fatores que a influenciam - Pallone, Leticia Valerio (Universidade Federal de São Carlos, 2019)
Introduction: Adequate hormonal and nutritional levels during fetal development and early postnatal period are critical for the proper development of the central nervous system (CNS). Studies suggest a developmental impairment and myelination of the auditory system, part of the CNS, associated with iron deficiency (ID) and congenital hypothyroidism (CH), which can be detected in the neonatal period through BERA (Brainstem Evoked Response Audiometry). Objectives: To analyze the relationship between latent iron deficiency (LID) and thyroid stimulating hormone (TSH) values with auditory nerve myelination in the newborn (NB) evaluated by BERA. Methodology: Cross-sectional, quantitative study developed at the Santa Casa de Misericórdia Maternity Hospital in São Carlos, Brazil, on a convenience sample, from August 2016 to January 2018. Sixty-five newborns were evaluated, and 165 of them were BERA. The levels of ferritin and hematocrit were measured. The TSH values were recovered from the neonatal screening tests of the newborns. The same professional who did not have previous access to the results of the blood tests performed BERA exams in the neonatal period. For the analysis of the relationship between LID and BERA latencies, the newborns were divided into two groups: control group (n = 71), with ferritin greater than 75 ng / ml; and LID group (n = 38), with ferritin between 11 and 75 ng / ml. In view of the TSH results, the study participants were divided into two groups: Group 1 (n = 35): TSH between 0 and 5 μIU / L; and Group 2 (n = 27): TSH between 5 and 15 μUI / L. Statistical analyzes were done by GraphPad Prism and SPSS 24 (IBM). The level of significance was 5%. Results: The percentage of congenital anemia was 26.4% and that of LID was 29.4% among those without anemia. The LID NB group showed a significant increase in V-latency and I-III, I-V, and III-V intervals in relation to the control group. These parameters showed a significant and negative correlation with ferritin. The multiple correlation analysis showed a significant correlation between the presence of LID and the latencies of the I-III and III-V intervals, even taking into account the gestational age of the newborn. There was no significant difference in the BERA scores between the groups with different TSH levels or a significant correlation between the TSH levels of the neonatal screening test and the values of the BERA waves and intervals. Conclusions: The results of this study demonstrated a negative effect of LID on the conductivity and myelination of the auditory pathways of the affected NB. On the other hand, in this study, no significant differences were found in wave latencies and BERA intervals between groups with different TSH values. Although insufficient evidence has been found to support a change in the TSH cutoff value for CH, the results of the present study may contribute to the discussion about the best value to be adopted by the national neonatal screening program and its impact on the development of the CNS.
Evaluation of the myelination of newborn hearing system and factors that influence it
Keywords: Recém-nascido; Ferritina; Deficiência latente de ferro; TSH; BERA; Newborn; Ferritin; Latent iron deficiency; CIENCIAS DA SAUDE::MEDICINA